2018
DOI: 10.3390/admsci8030037
|View full text |Cite
|
Sign up to set email alerts
|

Assembling Frameworks for Strategic Innovation Enactment: Enhancing Transformational Agility through Situational Scanning

Abstract: Although a significant body of knowledge has been created around strategic management that drives change and innovation, there are voids in the literature regarding assembling a flexible and localized environmental scanning (ES) framework needed to assess threats, opportunities, the current environment, and the desired end-state of a global value chain (GVC) with direct linkages to strategic enactment. In this paper, the author describes this gap and develops a capability to create a task plan from a situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 120 publications
(147 reference statements)
0
9
0
Order By: Relevance
“…The study is based on dynamic capability theory, and previous models that have clarified the relationship between either intellectual capital or SES and innovation (e.g. Leitner, 2011; Pizarro-Moreno et al ., 2011; Subramaniam and Youndt, 2005; Bigley, 2018; Nylén and Holmström, 2015). The findings have revealed that, in the kind of dynamic environmental conditions caused by COVID-19, which are expected to continue in the medium to long term, OCA has a significant impact on SIC and SES and the mediating path are also significant.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study is based on dynamic capability theory, and previous models that have clarified the relationship between either intellectual capital or SES and innovation (e.g. Leitner, 2011; Pizarro-Moreno et al ., 2011; Subramaniam and Youndt, 2005; Bigley, 2018; Nylén and Holmström, 2015). The findings have revealed that, in the kind of dynamic environmental conditions caused by COVID-19, which are expected to continue in the medium to long term, OCA has a significant impact on SIC and SES and the mediating path are also significant.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This requires resource agility (Martinez-Sanchez et al. , 2021), which relies on knowledge acquisition and creativity as well as the intellectual capital embedded in an organisation (Bigley, 2018; Li et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations